Evaluating the Quality of Pain Management Satisfaction Among Oncology Patients in a Hospital Setting: Psychometric Properties of the Arabic Version of Pain Care Quality Survey - Nijmeh Al-Atiyyat; Nezar Ahmed Salim; Jia-Wen Guo; Mohammed Toffaha; Jeannine M. Brant (JCO Global Oncology, 2023)
PURPOSEThe purpose of this mixed-methods psychometric study was to translate and adapt the Arabic Pain Care Quality (APainCQ) Survey to Arabic and to measure the quality of pain care provided to Arab patients.PATIENTS AND METHODSThis study used an iterative, mixed-methods approach that employed cognitive interviews, expert content analysis, and factor analysis to develop the APainCQ Survey. The study was conducted at Dubai Hospital, Dubai Health Authority, United Arab Emirates. Arabic-speaking patients admitted to the oncology/hematology inpatient units with a minimum 24-hour stay were eligible for the study.RESULTSThe sample consisted of 155 patients. The iterative exploratory factor analysis process resulted in the sequential removal of three items. The results of the significant Bartlett test (P < .001) of sphericity and Kaiser-Meyer-Olkin test of 0.93 for both the health care team scale and the nurse scale. The total variance explained was 76.17% for the health care team scale and 60.91% for the nurse scale, which explained 56.51% for factor 1 with 14 items and 4.40% for factor 2. Regarding internal consistency reliability, Cronbach's alpha and McDonald's omega for the health care team scale and nurse scale were high; both values were .95. Internal consistency reliability of pain assessment and pain management subscales of nurse scales were also high, with values of 0.96 and 0.79, respectively. Moreover, there was a moderate correlation (r = 0.66; P < .001) between the two subscales in the nurse scale.CONCLUSIONThis study provides evidence that the APainCQ is a reliable and valid measure of pain dimensions, including pain management and monitoring. This APainCQ scale can potentially expand research and clinical assessment in the Arab world.